Mineralogical, geochemical, and magnetic signatures of surface sediments from the Canadian Beaufort Shelf and Amundsen Gulf (Canadian Arctic) - Gamboa, Adriana; Montero-Serrano, Jean-Carlos; St-Onge, Guillaume; Rochon, André; Desiage, Pierre-Arnaud (Geochemistry, Geophysics, Geosystems, 2017)
Mineralogical, geochemical, magnetic, and siliciclastic grain‐size signatures of 34 surface sediment samples from the Mackenzie‐Beaufort Sea Slope and Amundsen Gulf were studied in order to better constrain the redox status, detrital particle provenance, and sediment dynamics in the western Canadian Arctic. Redox‐sensitive elements (Mn, Fe, V, Cr, Zn) indicate that modern sedimentary deposition within the Mackenzie‐Beaufort Sea Slope and Amundsen Gulf took place under oxic bottom‐water conditions, with more turbulent mixing conditions and thus a well‐oxygenated water column prevailing within the Amundsen Gulf. The analytical data obtained, combined with multivariate statistical (notably, principal component and fuzzy c‐means clustering analyses) and spatial analyses, allowed the division of the study area into four provinces with distinct sedimentary compositions: (1) the Mackenzie Trough‐Canadian Beaufort Shelf with high phyllosilicate‐Fe oxide‐magnetite and Al‐K‐Ti‐Fe‐Cr‐V‐Zn‐P contents; (2) Southwestern Banks Island, characterized by high dolomite‐K‐feldspar and Ca‐Mg‐LOI contents; (3) the Central Amundsen Gulf, a transitional zone typified by intermediate phyllosilicate‐magnetite‐K‐feldspar‐dolomite and Al‐K‐Ti‐Fe‐Mn‐V‐Zn‐Sr‐Ca‐Mg‐LOI contents; and (4) mud volcanoes on the Canadian Beaufort Shelf distinguished by poorly sorted coarse‐silt with high quartz‐plagioclase‐authigenic carbonate and Si‐Zr contents, as well as high magnetic susceptibility. Our results also confirm that the present‐day sedimentary dynamics on the Canadian Beaufort Shelf is mainly controlled by sediment supply from the Mackenzie River. Overall, these insights provide a basis for future studies using mineralogical, geochemical, and magnetic signatures of Canadian Arctic sediments in order to reconstruct past variations in sediment inputs and transport pathways related to late Quaternary climate and oceanographic changes. -- Keywords : mineralogy elemental geochemistry magnetic properties surface sediment sediment provenance ...